Polyethylene glycol mediated drought stress impacts on germination, growth and accumulation of proline in rice (Oryza sativa L.): Drought stress impacts in rice (SAARC Journal of Agriculture, 2022)
Drought is one of the major stress factors affecting the growth and development of plants, and is responsible for considerable crop yield losses worldwide. An experiment was conducted to compare three rice (Oryza sativa L.) varieties (BRRI dhan49, BRRI dhan71 and BRRI dhan75) for drought tolerance based on some growth parameters and physiological status in germination stage. Drought stress was imposed by five levels of polyethylene glycol (PEG) (0%, 10%, 15%, 20% and 25%). Rice varieties showed good germination with PEG concentration up to 15%. At 20% PEG concentration, a sharp reduction in germination percentage was observed and the highest germination percentage (55.53%) was found in the variety BRRI dhan71. Seeds of all the varieties treated with 25% PEG did not germinate. Seedling growth in terms of plumule and radicle length, fresh weight and dry weight decreased with increasing drought stress in all the varieties. Among the varieties, BRRI dhan71 was found to be the best at 20% PEG for seedling growth. Drought stress treatments decreased seedling length and weight vigor index in rice, whereas the highest seedling length and weight vigor index were obtained from BRRI dhan71. Accumulation of proline increased along with the increase of PEG concentration. The highest proline accumulation (3.08 mmol g-1 leaf) was obtained from the BRRI dhan71 at the higher treatment (20% PEG). This result suggests that BRRI dhan71 showed best performance under drought stress because of its own nature of tolerance. SAARC J. Agric., 20(1): 107-119 (2022)